Frequency reconfigurable monopole antenna with harmonic suppression for IoT applications - Alaa Imran AL-Muttairy; Malik Jasim Farhan (Universitas Ahmad Dahlan, 2020)
This work proposes a new reconfigurable printed monopole antenna for IoT devices working with the promising wireless technology Wi-Fi 6. Based on effective resonant length value, the antenna has the ability to reconfigure its operating band between 2.4 GHz and 5 GHz ISM bands. Therefore, the designed antenna works as an RF band-pass filter which reduces receiver complexity and supports network scalability. One PIN diode with complete biasing circuit is integrated to the antenna radiator to obtain re-configurability. Furthermore, two stubs are added to the antenna structure in order to suppress harmonic component which appears near to the higher band (5 GHz) when antenna forced to work at the lower band (2.4 GHz). The design built over commercially available FR-4 substrate with a compact size of (33.5x16x1.6) mm3. CST software is used to simulate antenna performance in terms of flection coefficient, radiation pattern, efficiency, and gain.